Review paperThe most common diseases of scalp in childhood - Lis-Święty, Anna; Wcisło-Dziadecka, Dominika; Wyględowska-Kania, Mariola (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2009)
The total and partial lack of hair growth occurs in the form of several clinical forms, either as an isolated defect or in connection with many kinds of abnormalities. Logical classification should be based on careful histopathological and genetic studies, but such studies are, unfortunately, rarely carried out. Hair microscopic examination is necessary in cases of abnormal hair, regardless of the quantitative which was on the scalp and it should be carefully sought for other ektodermal defects and examination of the patients relatives. Congenital alopecia may be partial or total. I the moment of the damage the condition of hair on the head is correct but tends to fall between the first and the sixth mouth after. Then it grows not at all or very irregularly. Lanugo type of hair, eyebrows and eyelashes may be absent. Teeth and nails are in order and the general state of health also. Total alopecia is caused by a congenital absence of hair follicle and microscopic examination reveals a lack of hair follicle. The paper presents the most common congenital alopecia, scaring and non scaring alopecia, and alopecia caused by mechanical factors. The rest of the work deals with structural hair disorders with increased breaking and without its presence.